Use of extracorporeal membrane oxygenation in tracheal surgery: a case series. (March 2014) - Chang, X; Zhang, X; Li, X; Xu, M; Zhao, H; Fang, W; Yao, F
Objectives: To review our experience of extracorporeal membrane oxygenation in airway management during tracheal surgery. Methods: A retrospective, observational study was conducted to evaluate the effectiveness of extracorporeal membrane oxygenation in tracheal surgery in Shanghai Chest Hospital between 2008 and 2012. Results: In all 91 tracheal surgeries, 7 high-risk cases used extracorporeal membrane oxygenation. The duration of extracorporeal membrane oxygenation support ranged from 10 min to 31 min. All extracorporeal membrane oxygenation patients underwent surgical procedures safely and there was no hospital mortality. Conclusions: Although various advanced anesthesia techniques can ensure a safe airway in tracheal surgery in most cases, extracorporeal circulation plays an important role in high-risk cases.